1996
DOI: 10.1021/es9406288
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Sorption of Naphthalene, Phenanthrene, and Pyrene to Low Organic Carbon Aquifer Sediments

Abstract: Sorption experiments were conducted with naphthalene, phenanthrene, and pyrene on low organic carbon sediments at 4 and 26 °C using batch and column techniques. Experimental controls ensured the absence of biologic and photolytic activity and colloidfree solution supernatants. Equilibrium distribution coefficients (K d ) increased 1.1-1.6 times with a decrease in temperature of 22 °C. Fraction instantaneous sorption (F) values did not change significantly with a decrease in temperature of 22 °C. Desorption rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
64
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 50 publications
8
64
0
1
Order By: Relevance
“…The use of temperature as a system variable Chemosphere 49 (2002) [569][570][571][572][573][574] www.elsevier.com/locate/chemosphere could give fundamental information about the twophase transport properties. Thermodynamic enthalpy is important to understand the process, and has been applied to the sorption process in the batch equilibrium method (Chiou et al, 1979(Chiou et al, , 1983Wauchope et al, 1983;Woodburn et al, 1989;Goss, 1992), but little work has been done concerning the effect of temperature on the transport process in soil columns (Piatt et al, 1996). The theoretical temperature dependence of the retention factor (k 0 ) of a solute is given by the vanÕt Hoff equation (Gilpin and Squires, 1981;Woodburn et al, 1989):…”
Section: Introductionmentioning
confidence: 99%
“…The use of temperature as a system variable Chemosphere 49 (2002) [569][570][571][572][573][574] www.elsevier.com/locate/chemosphere could give fundamental information about the twophase transport properties. Thermodynamic enthalpy is important to understand the process, and has been applied to the sorption process in the batch equilibrium method (Chiou et al, 1979(Chiou et al, , 1983Wauchope et al, 1983;Woodburn et al, 1989;Goss, 1992), but little work has been done concerning the effect of temperature on the transport process in soil columns (Piatt et al, 1996). The theoretical temperature dependence of the retention factor (k 0 ) of a solute is given by the vanÕt Hoff equation (Gilpin and Squires, 1981;Woodburn et al, 1989):…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have been performed in order to evaluate the effect of temperature on the desorption of "fresh" added PAHs into the soil/sediment. Piatt et al (1996) have observed that the desorption of PAHs from the low organic carbon sediments is favoured as the temperature increases. On the other hand, the temperature effect on the desorption of PAHs significantly increased when considering naturally contaminated soil (Enell et al 2005).…”
mentioning
confidence: 98%
“…Sorption is also the primary physico-chemical process affecting the transport, biodegradability, and bioavailability of many hydrophobic organic chemicals, including PAHs, in soils and sediments (Piatt et al 1996;Ortega-Calvo et al 1997;Reemtsma & Mehrtens 1997). The extent of the PAH sorption-desorption in soils and sediments depends strongly on the hydrophobicity of the solute and the total organic carbon content of the soil/sediment (Karickhoff et al 1979;Chiou et al 1998;Reeves et al 232 2004; .…”
mentioning
confidence: 99%
See 2 more Smart Citations